Historiographical Distortion of R.A Kartini's Heroism in a Feminist Sociological Perspective - Kenoba, Marianus Ola; Djandon, Maria Goretty (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The historiography of R.A Kartini 's heroism is a choice of topic that is quite challenging to discuss because Kartini is the only heroine who is armed with ideas. By tracing the historiography of Indonesian heroes, it was identified that not many of them left traces for the next generation in the form of written ideas. The monumental work that makes Kartini unique is a book titled “Letters of Javanese Princess.” The book “Letters of Javanese Princess” became a new milestone in the struggle of Indonesian women to gain access to formal education. The method used in this textual research is critical hermeneutics. The critical hermeneutics method allows a broad interpretation of written texts accessed by researchers. The results show that the historiography of Kartini's heroic values tended to be distorted by her rhetorical value alone. The impact is the occurrence of cults and devotional attitudes towards personality. The content of historical knowledge based on monumental historiography is quite risky because cults and devotions are always final, making it unnecessary to re-dialogue their existence. This research can be positioned as an auto criticism of Kartini's heroic historiography by utilizing the paradigm of feminist sociology.